IMPLEMENTASI PENDIDIKAN KARAKTER PERSPEKTIF KITAB TARBIYAH AS-SHIBYAN DI PONDOK PESANTREN AL-MAJIDIYAH PALDUDING PAMEKASAN MADURA - Maurusul Khoir (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2022)
This research was motivated by the existence of problems in the world of education, the weakness of learning and the existence of compulsion in learning. This behaviour can have a negative impact on the world of education. The purpose of research had three parts, First, to describe character education from the perspective of the book of Tarbiyah as-Shibyan at Pondok Pesantren al-Majidiyah Pamekasan, Madura. Second, to describe the supporting and inhibiting factors for implementing character education from the perspective of the book of Tarbiyah as-Shibyan at Pondok Pesantren al-Majidiyah Pamekasan, Madura. Third, to describe the implications of character education from the perspective of the book of Tarbiyah as-Shibyan at Pondok Pesantren al-Majidiyah Pamekasan, Madura. This type of research was a field research with primary data through interviews with administrators and teachers at al-Majidiyah. Secondary data from the literature, all data collected and analysed by qualitative methods, in a descriptive form. The results showed that the implementation of character education at the Al-Majidiyah Islamic Boarding School in three ways; First: The transformation of religious values in the cultivation of character education for small students. Second: The formation of a good personality in students. third: exemplary behavior for students. The supporting factor was the monitoring of the caretakers and administrators of the boarding house, strong support from the guardians of the students. the inhibiting factors are the age of the students who were too early and the lack of support from the guardians of the students. Penelitian ini dilatar belakangi adanya masalah di dunia pendidikan, lemahnya belajar dan adanya keterpaksaan dalam belajar. Prilaku tersebut dapat menodai kemurnian dunia pendidikan. Tujuan penelitian ini terdapat tiga bagian, Pertama, mendeskripsikan Pendidikan Karakter Perspektif Kitab Tarbiyah as-Shibyan di Pondok Pesantren al-Majidiyah Pamekasan Madura. Kedua, mendeskripsikan Faktor Pendukung dan Penghambat Implementasi Pendidikan Karakter Perspektif Kitab Tarbiyah as-Shibyan di Pondok Pesantren al-Majidiyah Pamekasan Madura. Ketiga, mendeskripsikan Implikasi Pendidikan Karakter Perspektif Kitab Tarbiyah as-Shibyan di Pondok Pesantren al-Majidiyah Pamekasan Madura.  Jenis penelitian ini merupakan penelitian lapangan dengan Data Primer melalui wawancara dengan pengurus dan guru di al-Majidiyah. Data sekunder dari literatur, semua data terkumpul dan dianalisis dengan metode kualitatif, dengan bentuk deskriptif. Hasil penelitian menyimpulkan impelementasi pendidikan karakter di Pondok Pesantren al-Majidiyah dengan tiga hal; Pertama: Transformasi nilai-nilai religius dalam penanaman pendidikan karakter bagi santri kecil. Kedua: Terbentuknya pribadi yang baik pada peserta didik. ketiga: Prilaku keteladanan bagi peserta didik. Faktor pendukung adanya pantauan dari pengasuh dan pengurus pesantren, dukungan kuat dari wali santri. faktor penghambatnya usia peserta didik yang terlalu dini dan kurangnya dukungan dari wali santri.